An Overview Of World Gold & Gold ETF Markets During And Post- Covid-19 Scenario - Dr.Susanta Kumar Mishra, Dr.Arka Kumar Das Mohapatra (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The sudden and unexpected Pandemic resulting from Corona Virus also known as COVID-19 casts a shadow on the world economic scenario. This situation was unexpected and beyond the preparedness of the mankind. As the pandemic was unexpected and is of a massive scale hence the plan to fight it was also low. This inability has resulted in huge loss for the financial sector around the world. As a result of the instability in the financial sector investors around the world returned in large numbers to the gold market, as a combination of macroeconomic drivers and kept interest in gold high. The authors are of the opinion that not only will gold remain highly relevant as a strategic portfolio component, but also six major trends will support demand for gold .The objective of this article is to find out the effect of this pandemic on the performance of the of the gold markets and the Gold ETF Sector during this period and to predict the future expected trend in coming days.